Lensing simulation and power spectrum estimation for high-resolution CMB polarization maps - Louis, T; Naess, S; Das, S; Dunkley, J; Sherwin, B (2013)
We present efficient algorithms for cosmic microwave background (CMB) lensing simulation and power spectrum estimation for flat-sky CMB polarization maps. We build a pure B-mode estimator to remedy E to B leakage due to partial sky coverage. We show that our estimators are unbiased, and consistent with the projected errors. We demonstrate our algorithm using simulated observations of small sky patches with realistic noise and weights for upcoming CMB polarization experiments. © 2013 The Authors Published by Oxford University Press on behalf of the Royal Astronomical Society.